An efficient gradient descent approach to separate a mixture of secondary surveillance radar replies based on disjoint component analysis - Sara Zaghloul; Nicolas Petrochilos; Mamadou Mboup (IET Radar, Sonar & Navigation)
Abstract The expansion of air traffic has led to an increase in mixed secondary surveillance radar (SSR) signal replies, which occur when multiple replies arrive at the receiver antenna simultaneously. These overlapping signals render the messages unrecoverable, leading to a loss of information. Additionally, the existing methods do not effectively address the issue of handling different types of signals with varying structures and characteristics. The authors validate the effectiveness of the disjoint component analysis (DCA) criterion for SSR signals and introduce a new DCA‐based algorithm designed to optimise the separation process. Through several simulations, the proposed algorithm demonstrates robust performance across various reception parameters. Additionally, it achieves good results when applied to real‐world data, showing its practical applicability and efficiency.